Persepsi Pengguna TikTok terhadap Hubungan Lagu “You Will Be in My Heart” dengan Ayat Al-Qur'an pada Akun GITA - Arina Vionarsih; Rafli Ardiansyah; Rifki Rahman Ferdian; Tasya Nur Fadhilah; Dadan Firdaus (Indo Publishing, 2026)
This study aims to analyze TikTok users' perceptions of the connection between the song